TREATMENT OF OPEN EXTRUDED FRACTURE NECK OF THE TALUS USING THE COMBINED METHOD OF EXTERNAL FIXATION MODIFIED FOR DYNAMIC ANKLE JOINT FIXATION AND KIRSCHNER WIRES - Božović, Aleksandar; Lalić, Ivica; Petrović, Dušan; Jovanović, Saša; Elek, Zlatan; Šipka, Aleksandar; Bojović, Marko (Sanamed, 2024)
Introduction: Open extruded fractures of the talus occur in 2% of talar fractures. These fractures are challenging for surgeons due to complications such as infection, nonunion, and arthritis. The most common treatment method is talus reimplantation and osteosynthesis. Case report: A 19-year-old presented with an open extruded fracture of the talus, classified as Hawkins II, following a fall from a height. Emergency surgery involved wound debridement, talus reimplantation, osteosynthesis with modified external fixation for dynamic ankle joint fixation (Mitkovic-type), and two Kirschner wires. Fragments were repositioned under C-Arm fluoroscopy. The patient received a 14-day antibiotic regimen (Cephalosporins, Aminoglycoside, Metronidazole) and thromboembolic prophylaxis for 35 days. After 6 weeks we allowed movements in the ankle joint with physical therapy. Gradual weight-bearing was allowed after 8 weeks. The osteosynthetic material was removed after 18 weeks, with full weight-bearing achieved after 6 months. Radiographic follow-up was conducted up to 24 months postoperatively, showing excellent healing with minimal dorsiflexion restriction. Conclusions: Treating this injury is a significant challenge. External fixation can be a viable method for managing open luxation fractures of the talus.